1997
DOI: 10.1021/jp963450f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Oxide Modification of Alumina on the Dispersion and Activity of Vanadia Catalysts

Abstract: Alumina was modified with 10 wt % MO x (MO x ) TiO 2 , ZrO 2 , La 2 O 3 , or MgO) prior to its impregnation with 12 wt % vanadia. The catalysts VTiAl, VZrAl, VLaAl, and VMgAl were characterized by X-ray diffraction (XRD), electron spin resonance (ESR), FT-Raman spectroscopy, 51 V solid state nuclear magnetic resonance ( 51 V NMR), and oxygen chemisorption. The activities of the catalysts were determined by methanol partial oxidation and their acid-base properties were evaluated for the decomposition of 2-propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This is consistent with the XPS work on vanadiaÈtitania catalysts performed by Chiarello et al17 and with the results on the formation of V4à ccording to Sawatzky et al 18 Furthermore, the presence of both octahedrally and tetrahedrally coordinated V species could play an important role. 19 However, the average binding energy value of V for the eroded, aged catalyst (515.7 eV) is even lower than the average value for V4`species (516.3 eV).11,17 This may be explained by the additional presence of lower oxidation states of vanadium as well as simply being caused by the argon ion bombardment. A more detailed and quantitative evaluation of the line shape broadening for the eroded catalysts is, therefore, hampered by the uncertainty in deÐning the extent to which the changes of the signals do actually reÑect mixed valency e †ects and how much of this broadening is simply due to an ion induced enhancement of defect structures and corresponding non-stoichiometry.…”
Section: Xps and Sims Resultsmentioning
confidence: 99%
“…This is consistent with the XPS work on vanadiaÈtitania catalysts performed by Chiarello et al17 and with the results on the formation of V4à ccording to Sawatzky et al 18 Furthermore, the presence of both octahedrally and tetrahedrally coordinated V species could play an important role. 19 However, the average binding energy value of V for the eroded, aged catalyst (515.7 eV) is even lower than the average value for V4`species (516.3 eV).11,17 This may be explained by the additional presence of lower oxidation states of vanadium as well as simply being caused by the argon ion bombardment. A more detailed and quantitative evaluation of the line shape broadening for the eroded catalysts is, therefore, hampered by the uncertainty in deÐning the extent to which the changes of the signals do actually reÑect mixed valency e †ects and how much of this broadening is simply due to an ion induced enhancement of defect structures and corresponding non-stoichiometry.…”
Section: Xps and Sims Resultsmentioning
confidence: 99%
“…It has been shown that the addition of alkali modifier is said to be effective in improving a catalyst's behavior [1], enhances the acidic or basic character or impart thermal stability to the carrier [2]. Shen et al [3] who studied on support modification with additives such as K 2 O, MgO, La 2 O 3 , and SnO 2 found that these additives influence the number and nature of basic or acid sites on the support.…”
Section: Introductionmentioning
confidence: 99%
“…This crystallographic rearrangement decreases the catalytic activity and selectivity of vanadia/ titania toward partial oxidation products. To defeat such drawbacks, titania-silica composite supports, in the form of both mixed and layered oxides, are considered suitable materials for deposition of vanadia (Handy et al 1992;Dias et al 1997;Lakshmi et al 1997;Gutiérrez-Alejandre et al 1998;. Chemical promoters, such as K, Cu, Ru, Zn, etc.…”
Section: Introductionmentioning
confidence: 99%